Site selective C–H functionalization of Mitragyna alkaloids reveals a molecular switch for tuning opioid receptor signaling efficacy - Srijita Bhowmik (Nature Portfolio, 2021)
Mitragynine (MG) is an indole alkaloid from kratom plant that binds opioid receptors and as such presents a scaffold for the development of atypical opioid receptor modulators. Here, the authors report a synthetic method for selective functionalization of the C11 position of MG, and show that this position is essential for fine-tuning opioid receptor signaling efficacy.